Social Expression of the Java Community and the Relevance Education Through the Film "Lemantun" by Wregas Bhanuteja: A Study of Cultural Contextual Education - Krismonika Khoirunnisa; Sumarlam Sumarlam; Oktavia Winda Lestari; Mohamad Jazeri (Javanologi: International Journal of Javanese Studies, 2023)
This research is a qualitative-descriptive research. This study also uses two methods, namely descriptive and explanative. Both methods are used to describe and explain the phenomenon of social expression and cultural values of Javanese society in the film “Lemantun”. The phenomenon includes its form, purpose, and context.Given these paper, the researcher seeks to examine the social expressions and cultural values of the Javanese people through the film "Lemantun" by Wregas Bhanuteja. This study aims to find the relationship between social expression and cultural values that exist in Javanese society. Therefore, the purpose of writing this paper is (1) to find out what forms of social expression and cultural values can be learned from the film "Lemantun", (2) what interpretations are found in social expressions and cultural values.This study uses the film "Lemantun" as the data source. The data analyzed are utterances or sentences spoken by the players. In this analysis, the researcher attempts to link social expressions and cultural values in the film by associating elements of Javanese culture in Indonesia, considering that the film "Lemantun" is a Javanese-language film entitled "Wardrobe".The results of this study include the discovery of social expressions and cultural values that exist in Javanese society. This research also seeks to find out how the Javanese people think and the real social etiquette.